Assessment of end products of Ashwagandha (Withania somnifera) and their marketing channel in Bharatpur, Chitwan, Nepal - K.C., Binita; Kafle, Gandhiv (Journal of Agriculture and Natural Resources, 2024)
This study was conducted for six month from February-July in 2019 to evaluate the end products, end uses, ingredients and marketing channel associated with Ashwagandha (Withania somnifera) in Bharatpur, Chitwan, Nepal. A 100% sampling intensity was employed encompassing all medicinal/herbal retailer shops and processing industries/companies identified within the study area. Data were collected through complete surveys of herbal/medicinal shops and industries located at Bharatpur city by using structured questionnaire which offered 41 end products containing W. somnifera as an ingredient. Additionally, two herbal industries were found, producing six types of Ayurvedic medicines using W. somnifera as a key ingredient. The major uses of these Ayurvedic medicines were found to treat illness of physical weakness (n=20), nervous system (n=18) and reproductive system (17). Of total end products 31.7% were solely made only from Ashwagandha and remaining were prepared by using other 187 medicinal plants/minerals or its extract as ingredient out of which Kurilo (Asparagus racemosus) was the most used medicinal plant as ingredient with it. Most of products were Classical Ayurvedic Medicine (51.22%) and sold without prescription (65.85%) also. Most of them were manufactured within Nepal (75.61%) but depends on Indian market for raw material of Ashwagandha. These products from manufacturing industries reached to medicinal/herbal retailer shops through stockiest and super stockiest and sometimes directly from Nepalese company via courier and marketing agents. Major challenges of W. somnifera processing industries is lack of cultivation of this species in Nepal leading their dependency on India for raw material, lack of incentives, difficult bureaucracy and political instability.